(untitled) (Anclajes, 2024)
Why should we ask ourselves about Baroque’s meaning? In fact, ¿can we define it? During the 20th century -and specially for the last thirty years- Baroque has been one of the most studied and discussed issues. It remains an inevitable topic when thinking about Latin-American literary and critical history. Two questions have driven, mainly but unequally, its interest: one referred to its concept, the other to its corpus. Thus, the relations between concept and corpus -be they understated or self-evident- remain frequently unattended or implicit. This paper aims to reexamine and clarify the concept of Baroque following its critical drifts, specially the literary ones and mostly for Latin America. It also aims to thoughtfully analyze several excerpts from the work of sor Juana Inés de la Cruz (Mexico, 1648-1695) and from Juan de Espinosa Medrano (Peru, ¿1630?-1688) that makes it possible to properly analyze the relationship between concept and corpus. Finally, it aims to clarify this relationship and the critical conditions in which it emerged in order to think a possible distinction between the seventeenth Baroque and the twentieth (Neo)Baroque.